‘Complexation’ of Palm Oil in Indonesia: The Actors and Their Involvement in North Mamuju, West Sulawesi - Mukrimin, Mukrimin (Forest and Society, 2022)
This research examines the complexity of many significant changes in Indonesia's palm oil (PO) industry in North Mamuju, West Sulawesi, focusing on the actors' involvement. The PO commerce in this country continues to grow due to the increasing demand for crude palm oil (CPO) and kernel palm oil (KPO), low labor costs, vast lands, tropical climate, soil conditions, as well as domestic and global demand. Furthermore, private firms and smallholders continue to dominate the OP sector with continuous growth from upstream to downstream. This suggested that the PO industry has substantially impacted and helped change the newly constituted district of West Sulawesi, North Mamuju, by applying ethnographical modes of inquiry. According to the actors, the complexity of PO industry in this region is simply driven by the dynamics of the frontier inside and beyond PO plantations zona. Secondly, they are committed to ensuring that the region continues to be a center of PO industry to stimulate economic development in Sulawesi. Empirically, investment requirements and community attractiveness to PO continue to persuade local governments that the sector is the only development path. Local actors envision North Mamuju as the future hub for PO farmers in the East Indonesian region.